Mineral density of skeletal bones in persons participating in northern complex sports - Kuchin R.V.; Nenenko N.D.; Stogov M.V.; Tolokova M.P. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to evaluate the mineral density of bone tissue of skeletal segments in young men involved in northern all-around events. Methods and structure of the study. Bone mineral density was studied in 24 young men aged 19-23 years, place of birth and place of permanent residence - Khanty-Mansi Autonomous Okrug-Yugra. The experimental group (EG) (n=12) included young men involved in the national sport - northern all-around (average age: 22,1±0,7 years), experience in sports 6-8 years. The control group (CG) (n=12) included young men who do not regularly engage in physical education and sports (average age 21,8±0,8 years). Using dual-energy X-ray absorptiometry, the mineral density of the bones of the skeleton and its segments, as well as the total content of minerals in them, was determined. Results and conclusions. The total mineral content and total mineral density of skeletal bones did not reveal statistically significant differences between the control and experimental groups. In the EG subjects there was a statistically significant (p<0,05) increase in the mineral density of the bones of the pelvis, spine and lower extremity bones, respectively, by an average of 5,7%, 5,4% and 6,6%. Statistically significant (at p<0,05) increased values ​​of the level of mineral density and the level of mineralization of the proximal femur and lumbar vertebrae (L1-L5) were found in the subjects of the experimental group relative to the control group. It is recorded that in young men involved in northern all-around, an area of ​​increased mineral density of skeletal bones is formed within the boundaries of the lumbar spine - the pelvic girdle - the proximal femur. In young men involved in northern all-around, in contrast to those who do not regularly engage in sports, an increase in bone mineral density is observed in certain segments and zones of the skeleton, forming a special support zone.